Systematic review of risks hidden in VR-based learning environments: Research frameworks and evidence from the literature - Yu-Ju Lan, Kai-Yu Tang (Educational Technology & Society)
Research into the use of virtual reality (VR) for educational purposes is increasing, but most of the existing literature focuses on the positive effects of VR on users, with its possible negative effects remaining underexplored. An inadequate understanding of the negative effects can put users at risk. To address this research gap, the main purpose of this study is to characterize the negative effects of VR use by conducting a systematic review of the literature published in the last decade (2010-2023). Web of Science and Scopus were searched using two sets of keywords. Following PRISMA, 20 studies were analyzed and identified five main categories of negative effects of VR in the research taxonomy of the coding scheme: physical, psychological, cognitive, behavioral symptoms, and cybercrime. The number of publications reporting the negative effects of VR was largest in 2020, followed by 2023, 2015, and 2016. Data were collected mostly using subjective methods, including questionnaire surveys and interviews. Based on the results, a series of frameworks are proposed for future research: VR addiction, reality–virtuality harmony, and VR navigation frameworks. Implications for educators, parents, and future researchers are provided.